Pemetaan rantai pasok jeruk siam (citrus nobilis) menggunakan analisis nilai tambah dan analisis struktur logistik - Fitriana Dina Rizkina; Ara Nugraha Nalawati (AGROINTEK, 2022)
Siamese citrus production in East Java is a potential agricultural business. Mapping the supply chain of Siamese oranges will be the first step for further supply chain improvements. This study aimed to describe the mapping of the supply chain structure of Siamese oranges through value-added analysis and logistics cost analysis to map the distribution of income between supply chain tiers. The total number of respondents in this study was 45 people. This study used descriptive analysis with convenience and snowball sampling to understand the objective picture. This study also used value-added analysis using the Hayami method and logistic cost analysis using the Activity Based Costing method. This research showed that the tiers involved in the supply chain were farmers, collectors, wholesalers, small traders, and consumers. Each supply chain tier had different added value and margin. The calculation of logistics costs showed material handling costs as the highest cost of the overall cost of the Siamese orange supply chain tiers. Recommendations from the results of this study were that an efficient and responsive post-harvest handling effort was needed at the farmer tier and the application of a pull supply chain in this Siamese orange supply chain system